The Power of Surrender: The Role of Tawakal in Building Academic Resilience among Indonesian High School Students - Difa Fatwa Fadlillah; Hazhira Qudsyi (Education Policy and Development, 2025)
Academic resilience refers to a student’s ability to overcome academic stress, adapt to challenges, and persist in achieving goals despite setbacks. One of the internal factors contributing to resilience is spirituality, including the concept of tawakal, the Islamic belief of surrendering to Allah after making an effort. This study aims to examine the relationship between tawakal and academic resilience among Muslim high school students in Indonesia. Using a quantitative correlational design, data were collected from 268 students across various regions using the Academic Resilience Scale and the Tawakal to Allah Scale. Results from the Spearman Rho test indicated a significant positive correlation between tawakal and academic resilience (r = 0.331, p < 0.01), with tawakal accounting for 11.5% of the variance in academic resilience. These findings highlight the role of Islamic spiritual values in supporting students’ psychological strength in academic settings. The study contributes to the development of context-specific models of resilience and provides practical implications for educators to integrate spiritual development into school-based character education programs.